EBV-associated ulceration in an immunocompromised patient. Issue 7 (July 2018) - Griffin, Jon; Allsobrook, Olive; Khurram, Syed Ali; Hegarty, Anne; Morley, Nick J.; Fernando, Malee
Abstract: Epstein Barr virus-positive mucocutaneous ulceration (EBVMCU) is an uncommon entity first described in 2010. This lymphoproliferative disorder was first described in immunocompromised patients presenting with well-defined ulceration involving the oral cavity, skin and gastrointestinal tract. The first case series suggested that EBVMCU is generally self-limiting and likely to resolve without treatment. However, since then, additional cases reported have described a more heterogeneous course. Many people are infected with Epstein Barr virus (EBV) at a young age and this usually has a self-limiting course. However, immunosuppression due to any cause, including age-related immunosenescene may facilitate a wide spectrum of EBV-related lymphoid hyperplasia and lymphoma. We describe a case of oral presentation of EBVMU in a patient on long term immunosuppressants.